2014
DOI: 10.1002/cctc.201402063
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation of Olefins Catalyzed by a Molecular Iron N‐Heterocyclic Carbene Complex: Influence of Reaction Parameters on the Catalytic Activity

Abstract: The catalytic epoxidation of olefins by an iron(II) complex bearing a tetradentate bis(pyridyl‐N‐heterocyclic carbene) ligand was investigated. This is the first example of the use of an organometallic iron compound (i.e., with a FeC bond) as an olefin epoxidation catalyst. The catalyst system, used without additives, showed good epoxide yields and selectivity for various olefins after a reaction time of 5 min. It was found that the epoxide yield strongly depended on the amount of the peroxide used and its na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…152 The ferrous complex [Fe II (71a)(CH3CN)2](PF6)2 was the first organometallic iron compound to be used as olefin epoxidation catalyst and also exhibits high efficiency in the oxygenation alkanes with H2O2 as the oxidant. 153,154 Under ambient conditions and at low catalyst loadings cyclohexane is oxidised with up to 32 turnovers and high selectivity towards the formation of cyclohexanol and cyclohexyl hydroperoxide ((A + H)/K = 19). Substitution of one of the axial acetonitrile units by a phosphine or isonitrile ligand stabilises the catalyst under oxidising conditions without altering the selectivity, which translates to increased turnovers.…”
Section: Iron Nonheme Complexes Bearing C- O-and S-donor Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…152 The ferrous complex [Fe II (71a)(CH3CN)2](PF6)2 was the first organometallic iron compound to be used as olefin epoxidation catalyst and also exhibits high efficiency in the oxygenation alkanes with H2O2 as the oxidant. 153,154 Under ambient conditions and at low catalyst loadings cyclohexane is oxidised with up to 32 turnovers and high selectivity towards the formation of cyclohexanol and cyclohexyl hydroperoxide ((A + H)/K = 19). Substitution of one of the axial acetonitrile units by a phosphine or isonitrile ligand stabilises the catalyst under oxidising conditions without altering the selectivity, which translates to increased turnovers.…”
Section: Iron Nonheme Complexes Bearing C- O-and S-donor Ligandsmentioning
confidence: 99%
“…125 As already mentioned for alkane oxidation reactions, iron-NHC complex [Fe II (71a)(CH3CN)2](PF6)2 was also applied for the oxygenation of aromatic substrates with H2O2 as the oxidant. 153,190 In the presence of 1 mol% catalyst benzene and toluene are converted to phenols in yields of 11.2 and 14.7% respectively. In the case of toluene a high selectivity for aromatic instead of benzylic oxidation is observed.…”
Section: Iron Nonheme Complexes Bearing C- O-and S-donor Ligandsmentioning
confidence: 99%
“…Selected known NHC/N-donor proligands are shown in Figure 1 and range from tri-and tetradentate macrocyclic systems, [H 2 L 1 ] 2+28 or [H 2 L 2 ] 2+ , 29 to pentadentate NHC/py 4 ligands [HL 3 ] + , 30 tetradentate bis(NHC)s [H 2 L 4 ] 2+ , 31 tridentate NHC/py 2 ligands [HL 5 ] + , 32 and pyridine-or pyrimidine-substituted imidazolium salts like [HL 6 ] + . 32b, 33 As an example of the beneficial use of such hybrid ligands in iron chemistry, we note that the ferric complex of the open chain NHC/pyridine ligand L 4b has been shown to serve as a catalyst for aromatic hydroxylation 34 and olefin epoxidation 35 reactions.…”
mentioning
confidence: 99%
“…7−9 Examples of remarkable reactivity were obtained on the basis of the use of chelating, polydentate NHC ligands, 10−17 including oxidation catalysis with NHC/pyridine hybrid ligands. 18,19 Recently, it could be shown that replacing acetonitrile ligands of the catalytically active iron(II) NCCN complex has a strong influence on the electronic structure of the metal center. 20 However, the literature lacks comprehensive studies on the influence of NHC/pyridine hybrid ligands with different NHC/pyridyl ratios on the oxidation potential of the metal.…”
Section: ■ Introductionmentioning
confidence: 99%